EXPLORING THE INFLUENCE OF TEACHER SELF-EFFICACY ON JOB SATISFACTION IN SECONDARY SCHOOLS OF MUZAFFARABAD - Dr. Batool Atta; Inaamul Haq Mughal; Dr. Adeel Ahmed Khan (Review Journal of Social Psychology & Social Works, 2024)
This research paper investigates the dynamic relationship between teacher self-efficacy and job satisfaction in context of secondary schools Muzaffarabad. Recognizing fundamental role that teachers perform in influencing the educational experience, this study objectives to the impact of teachers’ beliefs in their capabilities on their overall job satisfaction. By employing a quantitative -methods approach through surveys of teacher self-efficacy also its correlation with job satisfaction. Methodologically, the research employs a 254 sample of secondary school teachers from Muzaffarabad, The researcher was used two instruments after written permission , Teacher Self-Efficacy Scale(The Ohio State Teacher Efficacy Scale), developed by Megan Tschannen-Moran and for analyzing teachers’ self-efficacy andJob Satisfaction Survey (JSS), created by Paul Spector .Quantitative data were statistically analyzed to identify patterns and correlations, The findings of this study aim to shed light on the specific factors within teacher self-efficacy that significantly impact job satisfaction, offering implications for educational policies and professional development programs. As education plays a essential role in societal development, understanding and improving the well-being of secondary school teachers can contribute to the overall improvement of the educational landscape in Muzaffarabad. Keywords- Teacher Self-Efficacy , Job Satisfaction , Secondary Schools, Muzaffarabad